Investigating the Secondary Thermal Neutron Intensity of Neutron Capture-Enhanced Proton Therapy - Takahiro Shimo; Shintaro Shiba; Hiroyuki Watanabe; Masashi Yamanaka; Kazuki Matsumoto; Akihiro Yamano; Hisato Nagano; Kohichi Tokuuye (Applied Sciences, 2025)
This study aimed to investigate the distribution of thermal neutron fluence generated during proton-beam therapy (PBT) scanning, focusing on neutrons produced within the body using Monte Carlo simulations (MCSs). MCSs used the Particle and Heavy Ion Treatment Code System to define a 35 × 35 × 35 cm3 water phantom, and proton-beam energies ranging from 70.2 to 228.7 MeV were investigated. The MCS results were compared with neutron fluence measurements obtained from gold activation analysis, showing good agreement with a difference of 3.54%. The internal thermal neutron distribution generated by PBT was isotropic around the proton-beam axis, with the Bragg peak depth varying between 3.45 and 31.9 cm, while the thermal neutron peak depth ranged from 5.41 to 15.9 cm. Thermal neutron generation depended on proton-beam energy, irradiated particle count, and depth. Particularly, the peak of the thermal neutron fluence did not occur within the treatment target volume but in a location outside the target, closer to the source. This discrepancy between the Bragg peak and the thermal neutron fluence peak is a key finding of this study. These data are crucial for optimizing beam angles to maximize dose enhancement within the target during clinical applications of neutron capture-enhanced particle therapy.